2012
DOI: 10.1063/1.4728216
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and stability of half-metallic ferromagnetism in alkaline-earth metal mononitrides against doping and deformation

Abstract: We employ ab-initio electronic structure calculations and study the magnetic properties of CaN and SrN compounds crystallizing in the rocksalt structure. These alkaline-earth metal mononitrides are found to be half-metallic with a total spin magnetic moment per formula unit of 1.0 µB. The Curie temperature is estimated to be 480 K for CaN and 415 K for SrN well-above the room temperature. Upon small degrees of doping with holes or electrons, the rigid-band model suggests that the magnetic properties are little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The p-orbital magnetism was intensively investigated in the compounds of (I,II)A-(IV,V,VI)A. Half-metallic ferromagnetism is predicted in compounds of CaC, SrC, and BaC with zinc-blende structure, 9 as well as with rocksalt structures. 8 The investigation is also extended to rocksalt and zinc-blende LiS, NaS, KS, 10 and NaN, KN, 11 alkaline earth selenides 12 as well as mononitrides, 13 pnictides. 14 In this work, electronic structures of alkaline earth carbides (M IIA C) are calculated.…”
Section: Introductionmentioning
confidence: 99%
“…The p-orbital magnetism was intensively investigated in the compounds of (I,II)A-(IV,V,VI)A. Half-metallic ferromagnetism is predicted in compounds of CaC, SrC, and BaC with zinc-blende structure, 9 as well as with rocksalt structures. 8 The investigation is also extended to rocksalt and zinc-blende LiS, NaS, KS, 10 and NaN, KN, 11 alkaline earth selenides 12 as well as mononitrides, 13 pnictides. 14 In this work, electronic structures of alkaline earth carbides (M IIA C) are calculated.…”
Section: Introductionmentioning
confidence: 99%
“…In two pioneering papers published by Geshi et al [13] and Kusakabe et al [14], it was shown using first-principles calculations that CaP, CaAs and CaSb compounds present half-metallic ferromagnetism when grown in the zincblende structure. Several first-principles calculations have been carried in several I/II-IV/V compounds and it was shown that they are half-metallic magnets in all three zincblende, wurtzite and rocksalt (rs) metastable structures; the ground state in all cases being the rs lattice [15][16][17]. In Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in the case of the semi-Heusler compounds like NiMnSb the total spin magnetic in the unit cell, M t scales, as a function of the total number of valence electrons, Z t , following the relation M t = Z t − 18 [21], while in the case of the L2 1 full-Heuslers this relation becomes M t = Z t − 24 [22]. Moreover for the TM pnictides and chalcogenides as well as the d 0 -ferromagnets the corresponding rule takes the form M t = Z t −8 although its origin is different in the two families of compounds [15,16,23] These Slater-Pauling (SP) rules connect the electronic properties (appearance of the half-metallic behavior) directly to the magnetic properties (total spin magnetic moments) and thus offer a powerful tool to the study of half-metallic compounds since (i) magnetic measurements can be used to confirm the half-metallic character of a compound, and (ii) simple valence electrons counting can predefine the magnetic properties of a half-metal. The aim of the present Short Review is to provide an overview of the origin of the SP rule in all mentioned families of half-metallic magnets as derived from electronic structure calculations based on the density functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…We can use our results to predict the substrates that match the lattice constants of our compounds with large magnetic moments, but we believe that this will not always be possible for large lattice constants or energies far from equilibrium; therefore, the issue of stability will be addressed later. Tetragonalization can also occur during growth, but it will not necessarily destroy half-metallicity [29]. In Table III, we present detailed ferromagnetic properties of the three compounds in the primitive cells of the three types of structures.…”
Section: Can the Three Half-heusler Alloys Be Ferromagnetic Or Halmentioning
confidence: 99%